Development of N,N-disulfo-1,1,3,3-tetramethylguanidinium Chlorometallates as Heterogeneous Catalysts for One Pot Synthesis of 1,2-dihydro-1- aryl-3H-naphth[1, 2-e][1,3]oxazin-3-one Derivatives - Dutta, Arup K.; Boruah, Kabita; Borah, Ruli (Current Organocatalysis, 2021)
Background: Four members of N,N-disulfo-1,1,3,3-tetramethylguanidinium chlorometallates [DSTMG]n[X], where n= 1 or 2; X= FeCl4 - , Zn2Cl62-, NiCl42-, MnCl42- were synthesized as solid Brønsted-Lewis acidic compounds and studied the catalytic activity with the most acidic salt for threecomponent synthesis of 1,2-dihydro-1-aryl-3H-naphth[1,2-e][1,3]oxazin-3-ones. Methods: N,N-disulfo-1,1,3,3-tetramethylguanidinium chlorometallates of the four transition metal cations such as Fe(III), Zn(II), Ni(II) and Mn(II) were prepared after treatment of the parent ionic liquid N,N-disulfo-1,1,3,3-tetramethylguanidinium chloride [DSTMG][Cl] with the respective metal chlorides in different mole fractions at 75 ºC. The synthesis of 1,2-dihydro-1-aryl-3H-naphth[1,2- e][1,3]oxazin-3-ones was carried out via three-component reaction of 2-naphthol, aromatic aldehydes and urea under neat condition at 90 ºC using 7 mol% of the [DSTMG][FeCl4] catalyst. Results: The characterization of synthesized chlorometallates was done using spectroscopic and other analytical techniques, including thermogravimetric analysis and Hammett acidity studies. Among the four salts, the salt of Fe(III) ion was observed as the strong Brønsted acidic hydrophobic salt and thus chosen for the catalytic study. Conclusion: A new type of chlorometallates of guanidinium cation with composition [DSTMG]n[X], where X= FeCl4- /Zn2Cl62-/ NiCl42-/ MnCl42- and n= 1 or 2 were developed as –SO3H functionalized solid acids with varied thermal stability (150-250 ºC) and physisorbed water (0-20%) as observed from the thermogravimetric study. From them, the most Brønsted acidic Fe(III) salt was employed as an efficient recyclable heterogeneous catalyst for the one-pot synthesis of 1,2-dihydro-1-aryl-3Hnaphth[ 1,2-e][1,3]oxazin-3-ones in neat condition.
Keywords: chlorometallates